PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI KECAMATAN SAMPANG KABUPATEN SAMPANG - Fatimah Riswati; Muninghar; Nur Aizeh (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
Nur Aizeh, 2021. The Effect of Training and Work Discipline on the Work Performance of Sampang District Employees, Sampang Regency. Postgraduate Program at Wijaya Putra University, Surabaya. The type of research is explanatory research, the approach used is a quantitative approach with a total sample of 94 respondents. The purposes of this study are 1) To describe the Training and Job Performance of Employees in Sampang District, Sampang Regency. 2) To test and analyze whether Training and Work Discipline have a significant simultaneous effect on Employee Work Performance in Sampang District, Sampang Regency. 3) To test and analyze whether training has a significant effect on employee performance in Sampang District, Sampang Regency. 4) To test and analyze whether Work Discipline has a significant effect on Employee Work Performance in Sampang District, Sampang Regency. The results of the study show that